Émergence insoumise: réflexions sur la persistance du racisme systémique envers les femmes autochtones - Wylde, Cyndy (Hannenorak, 2024)
« Émergence insoumise s'ouvre sur un souvenir de l'autrice qui attend un taxi après un colloque : « Non, mais croyez-vous vraiment que moi, une femme des Premières Nations, je vais aller attendre seule le soir, à Val-d'Or? » Ces mots, adressés au gardien qui lui indique que les portes de l'université sont sur le point de fermer, seront le catalyseur d'une réflexion sur le sort réservé aux femmes autochtones, aussi bien dans le milieu carcéral que dans la société canadienne en général. Alternant entre les réminiscences personnelles et les analyses du racisme systémique afin d'aller au-delà des statistiques et des préjugés, cet essai de Cyndy Wylde s'inscrit dans une tradition de littérature de combat, qui bouscule les idées reçues et dynamite le confort et l'indifférence. »
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; discours dominant; féminisme autochtone; phi4336; philosophie; premier cycle; privilèges; périodes historiques; québec; racisme; racisme systémique; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences

Feminism and the body - Schiebinger, Londa (Oxford University Press, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Section: IX, 500 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme